Petrochronology of Accessory Minerals in relation to Metamorphism and Fluid-Flow across the Albany-Fraser Orogen and Eucla Basement, Western Australia - Chard, Julian Alexander (Curtin University, 2019)
Petrochronology of uranium-bearing accessory minerals (zircon, monazite, rutile and titanite) across the Albany-Fraser Orogen and Eucla basement was undertaken to provide insight into transient metamorphism and fluid-flow events and their link to geodynamic triggers. This study includes the oceanic accretion of the Madura Province and crustal thickening, identifying a distal footprint to gold mineralisation related to Stage II of the Albany-Fraser Orogeny and mineral deformation within the Fraser Shear Zone.